Combined viscous dissipation and joule heating effects on chemically radiative MHD micropolar flow with heat source and convective boundary conditions - Konda, Jayaramireddy; Reddy, M. Narendranadh; Ganteda, Charankumar; Kottapalli, Rajyalakshmi; Adinarayana, Y.; Govindan, Vediyappan; Byeon, Haewon; Pimpunchat, Busayamas (My University, 2025)
The proposed study presents a comprehensive investigation of the combined effects of viscous dissipation and Joule heating on chemically reactive magnetohydrodynamic (MHD) micropolar fluid flow over a nonlinear stretching sheet, incorporating the influences of radiative heat transfer, heat source, and convective boundary conditions. The current study investigates the flow of a type of fluid called micropolar fluid in a stretched 2D space. This fluid is viscous, and the flow is influenced by convective boundary conditions. Mathematical equations are derived considering factors such as heat, friction, electrical effects, chemical reactions, and radiation heat transfer. The fluid can conduct electricity when exposed to an external magnetic field. The complex partial differential equations governing the boundary layer flow are simplified into ordinary differential equations using a technique known as similarity transformation. The problem is solved using the Runge-Kutta-Fehlberg method with a shooting technique. Graphs are generated to analyze how physical factors influence temperature and concentration profiles. The skin friction coefficient, local Nusselt number, and local Sherwood number are calculated and studied. In this study, we compare our results with those of other research and find good agreement.
Keywords: Chemical reaction; Convective boundary conditions; Heat source; Joule heating; MHD; Nonlinear stretching sheet; Thermal radiation